Ternary positive electrode material, preparation method thereof and electrochemical device

By employing gradient sintering and doping coating processes, the problems of high residual lithium and poor cycle stability in the preparation of ternary cathode materials have been solved, resulting in low-cost, high-energy-density, and long-cycle-life ternary cathode materials suitable for new energy batteries.

CN121439749APending Publication Date: 2026-01-30NANTONG RESHINE NEW MATERIAL TECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511588741.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-31
Publication Date
2026-01-30

AI Technical Summary

Technical Problem

Existing ternary cathode materials suffer from problems such as high residual lithium on the surface, poor cycle stability, and high preparation costs during the preparation process, which limit their large-scale production.

Method used

A gradient sintering process is adopted, and the temperature of the first sintering is controlled in stages. Combined with doping and coating processes, the residual alkali content is reduced by precisely controlling the temperature of each stage, forming a dense and uniform matrix material, and a coating layer is formed on the surface to improve structural stability and interface compatibility.

Benefits of technology

It reduces production costs, improves the crystal density and cycle stability of ternary cathode materials, enhances compatibility with solid electrolytes, and extends the cycle life and safety of electrochemical devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121439749A_ABST
    Figure CN121439749A_ABST
Patent Text Reader

Abstract

The invention discloses a ternary positive electrode material, a preparation method thereof and an electrochemical device. The preparation method comprises the following steps: mixing a ternary precursor, a lithium source and a doping material to obtain a first mixture; the first mixture is subjected to primary sintering, a base material is obtained, primary sintering comprises a first stage, a second stage, a third stage and a fourth stage which are conducted in sequence, the temperature of the first stage and the temperature of the fourth stage are both 0.3-0.4 time that of the third stage, and the temperature of the second stage is 0.7-0.8 time that of the third stage; and mixing the base material and the coating material to obtain a second mixture. According to the method, a gradient sintering schedule is adopted, the primary sintering is subjected to staged program temperature control, the lithium source and the ternary precursor are promoted to fully react in the primary sintering process, and the content of residual alkali is reduced, so that a water washing process can be omitted, the damage to the structure of the ternary positive electrode material is reduced, and the production cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of new energy technology, specifically to a ternary cathode material and its preparation method, and an electrochemical device. Background Technology

[0002] In recent years, with the rapid development of new energy vehicles and electronic products, consumer demand for lithium-ion batteries has been increasing. As a key component of lithium-ion batteries, the performance of cathode materials directly affects battery cycle stability, first-cycle coulombic efficiency, discharge capacity, and rate performance. Currently, ternary cathode materials occupy a mainstream position among lithium-ion battery cathode materials due to their advantages such as high energy density, long cycle life, and environmental friendliness.

[0003] However, existing ternary cathode materials still suffer from problems such as high residual lithium on the surface, poor cycle stability, and high preparation costs during the preparation process, which limit the large-scale production of ternary cathode materials. Summary of the Invention

[0004] In view of this, in order to solve at least one of the above technical problems, this application provides a method for preparing a ternary cathode material.

[0005] In addition, embodiments of this application also provide a ternary cathode material and an electrochemical device.

[0006] In a first aspect, embodiments of this application provide a method for preparing a ternary cathode material. The method includes the following steps: mixing a ternary precursor, a lithium source, and a dopant to obtain a first mixture; sintering the first mixture once to obtain a matrix material, wherein the first sintering includes a first stage, a second stage, a third stage, and a fourth stage performed sequentially, wherein the temperature of the first stage and the temperature of the fourth stage are both 0.3 to 0.4 times the temperature of the third stage, and the temperature of the second stage is 0.7 to 0.8 times the temperature of the third stage; mixing the matrix material and a coating material to obtain a second mixture; and sintering the second mixture a second time to form a coating layer on the surface of the matrix material, thereby obtaining the ternary cathode material.

[0007] Based on the first aspect, in some possible embodiments, the temperature of the third stage is 300℃~700℃, and the duration of the third stage is 20h~30h.

[0008] Based on the first aspect, in some possible embodiments, the temperature of the first stage is 200℃~260℃, and the duration of the first stage is 10h~15h; the temperature of the second stage is 460℃~520℃, and the duration of the second stage is 10h~20h; the temperature of the fourth stage is 200℃~260℃, and the duration of the fourth stage is 8h~15h.

[0009] Based on the first aspect, in some possible embodiments, the preparation method satisfies at least one of the following conditions: (1) the heating rate of the first mixture to the temperature of the first stage is 10℃ / min to 20℃ / min; (2) the heating rate of the mixture from the temperature of the first stage to the temperature of the second stage is 0.5℃ / min to 1℃ / min; (3) the heating rate of the mixture from the temperature of the second stage to the temperature of the third stage is 5℃ / min to 7℃ / min; (4) the cooling rate of the mixture from the temperature of the third stage to the temperature of the fourth stage is 0.5℃ / min to 5℃ / min.

[0010] Based on the first aspect, in some possible embodiments, after the fourth stage, the step of obtaining the matrix material further includes: cooling the matrix material in the furnace to 20°C~100°C.

[0011] Based on the first aspect, in some possible embodiments, the doping element in the doped material includes at least one of Si, B, and P.

[0012] Based on the first aspect, in some possible embodiments, the coating material includes a solid electrolyte.

[0013] Based on the first aspect, in some possible embodiments, the solid electrolyte includes at least one of a sulfide solid electrolyte, an oxide solid electrolyte, and a halide solid electrolyte.

[0014] Secondly, this application provides a ternary cathode material, which is prepared by the aforementioned preparation method. The ternary cathode material includes a matrix material containing doped elements and a coating layer located on the surface of the matrix material.

[0015] Thirdly, embodiments of this application also provide an electrochemical device, the electrochemical device including a positive electrode sheet, the positive electrode sheet including a positive electrode material, the positive electrode material being the aforementioned ternary positive electrode material.

[0016] Compared to existing technologies, the ternary cathode material preparation method provided in this application adopts a gradient sintering process with staged temperature control during the primary sintering stage. Firstly, by precisely controlling the temperature at each stage during the primary sintering process, the lithium source and ternary precursor react fully, reducing residual alkali content. This eliminates the need for a water washing process, avoiding damage to the ternary cathode material structure and reducing production costs. Secondly, gradient sintering allows for a more complete and uniform bonding of the ternary precursor, lithium source, and dopant materials, thereby improving the density and uniformity of element distribution in the ternary cathode material. Furthermore, the doping and coating processes synergistically enhance the structural stability and cycle stability of the ternary cathode material. Attached Figure Description

[0017] Figure 1 This is a process flow diagram of a method for preparing a ternary cathode material according to an embodiment of this application.

[0018] Figure 2 This is a comparison chart of the free lithium content in the ternary cathode materials of Examples 1-2 and Comparative Example 2 of this application.

[0019] Figure 3 This is a comparison chart of the high-temperature cycling performance of the ternary cathode materials in Examples 1, 1, and 3 of this application.

[0020] Figure 4 The images are scanning electron microscope (SEM) images of cross sections of the ternary cathode materials after 100 cycles in Examples 1 and 3 of this application. Detailed Implementation

[0021] The embodiments of this application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain this application, and should not be construed as limiting this application; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs; where there is no conflict, the implementation methods and features of the implementation methods of this application can be combined with each other; many specific details are set forth in the following description to provide a full understanding of this application, and the described implementation methods are only a part of the implementation methods of this application, and not all of the implementation methods.

[0022] The applicant's research found that there are two main problems in the synthesis process of ternary cathode materials (especially high-nickel ternary cathode materials for solid-state batteries).

[0023] The first problem is the high residual lithium content on the surface of ternary cathode materials. This is mainly due to the high sintering temperature and excess lithium source typically used during the preparation of ternary cathode materials to ensure sufficient reaction. While these conditions contribute to material formation, they also easily lead to the generation of impurity phases and residual lithium. When ternary cathode materials are exposed to air, the residual lithium on the surface reacts with CO2 and H2O in the air to form byproducts such as LiOH and Li2CO3. High residual lithium can also lead to slurry gelation (gelation refers to the slurry absorbing water and reacting with the binder PVDF), making the slurry difficult to process, increasing interfacial impedance, affecting lithium-ion transport, generating gas during cycling, and causing battery bulging. Currently, residual lithium removal from ternary cathode materials mainly uses water washing processes to remove residual lithium salts from the material surface through physical and chemical actions. However, water washing has some drawbacks: for example, ternary cathode materials are sensitive to water, and lithium salts may be generated during the water washing process. + / Ni 2+ Mixing leads to structural damage and capacity decay; washing dissolves some active lithium, resulting in lithium loss and affecting material capacity; parameters such as washing time, temperature, and stirring speed need to be precisely controlled, otherwise it can easily lead to performance differences between batches; the wastewater generated after washing has a complex composition, which increases wastewater treatment costs and technical requirements.

[0024] The second problem is that ternary cathode materials themselves have poor cycle stability, and the interface problems between them and solid electrolytes are severe. This is mainly because ternary cathode materials are more prone to irreversible phase transitions from the H2 phase (hexagonal 2-phase) to the H3 phase (hexagonal 3-phase) during electrochemical cycling. The significant change in volume anisotropy leads to a series of problems, including material structure degradation, microcrack formation, side reactions, and gas generation, resulting in a reduced cycle life of lithium-ion batteries. Furthermore, when ternary cathode materials come into contact with solid electrolytes (such as sulfides), due to the difference in their potentials and the spontaneous decomposition of sulfide solid electrolytes under high voltage, the interface is prone to problems such as interface side reactions, space charge layers, and element diffusion, leading to poor battery stability.

[0025] For this purpose, please refer to Figure 1 As shown in the embodiments of this application, a method for preparing a ternary cathode material is provided. This method uses a non-water washing process to reduce the residual lithium in the ternary cathode material while maintaining its good electrochemical performance and ensuring good compatibility between the ternary cathode material and the solid electrolyte. Specifically, the method includes the following steps: Step S1: Mix the ternary precursor, lithium source and dopant to obtain the first mixture.

[0026] Specifically, the ternary precursor, lithium source, and dopant containing doped elements are mixed evenly in a high-speed mixer in a certain proportion to obtain the first mixture.

[0027] Among them, adding a doping material to the first mixture is beneficial to improving the structural stability of the ternary cathode material through doping.

[0028] In some embodiments, the doping element in the doping material can be at least one of Si, B, and P. The doping material can be a compound corresponding to the doping element, such as B2O3, Si3P4, POCl4, etc. The doping element in the above doping material can form a strong bond with the oxygen element in the ternary precursor, improving the structural stability of the ternary cathode material.

[0029] In some embodiments, the chemical formula of the ternary precursor can be Ni x Co y Mn 1-x-y (OH)2, where 0.85 < x < 0.9 and 0.05 < y < 0.1. The nickel content in the ternary precursor satisfies 0.85 < x < 0.9, which is beneficial to improving the energy density of the ternary cathode material, reducing the cobalt consumption, and lowering the manufacturing cost of the ternary cathode material.

[0030] Step S2: Sinter the first mixture once to obtain a matrix material. The primary sintering includes a first stage, a second stage, a third stage, and a fourth stage carried out in sequence. Among them, the temperature of the first stage is 0.3 - 0.4 times the temperature of the third stage, and the temperatures of the second stage and the fourth stage are both 0.7 - 0.8 times the temperature of the third stage.

[0031] Adopting a gradient sintering regime, the primary sintering is temperature-controlled in stages. During the primary sintering process, by precisely controlling the temperature of each stage, it is promoted that the lithium source in the first mixture reacts fully with the ternary precursor, reducing the residual alkali content. Thus, the subsequent water washing process can be omitted, avoiding the damage to the structure of the matrix material caused by water washing and reducing the production cost. Moreover, the staged gradient sintering can also improve the uniformity and sufficiency of the reaction between the ternary precursor and the doping material, thereby improving the uniformity of the distribution of the doping element in the ternary cathode material, which is beneficial to better exerting the doping effect. In addition, precise gradient sintering can improve the densification and uniformity of the crystals of the matrix material.

[0032] Specifically, the temperature of the first stage (low-temperature stage) is 0.3 - 0.4 times the temperature of the third stage (high-temperature stage). The main purpose of this stage is to remove impurities in the ternary precursor and the lithium source, avoiding the generation of water vapor when these impurities decompose in the subsequent third stage. This is because the water vapor will react with the lithium source to generate LiOH, and this part of LiOH will melt and wrap the particles at high temperature, hindering the densification of the primary sintering and remaining on the surface in large quantities after cooling. Therefore, the first stage can remove impurities at low temperature, thereby reducing the surface residual lithium of the ternary cathode material and improving the densification of the crystals of the matrix material.

[0033] Specifically, the temperature of the first stage can be 200℃~260℃, which is beneficial for thoroughly removing impurities. The temperature of the first stage can, for example, be 200℃, 210℃, 220℃, 230℃, 240℃, 250℃, 260℃, or any value within the range of any two of the above values. The time of the first stage can be 10h~15h, which is beneficial for thoroughly preheating the first mixture and thoroughly removing impurities. The time of the first stage can, for example, be 10h, 11h, 12h, 13h, 14h, 15h, or any value within the range of any two of the above values.

[0034] In some embodiments, the heating rate for raising the first mixture to the temperature of the first stage can be 10°C / min to 20°C / min. A higher heating rate is beneficial for improving production efficiency and rapid heating. The heating rate can be exemplarily 10°C / min, 12°C / min, 15°C / min, 18°C / min, 20°C / min, or any value within the range of any two of the above values.

[0035] The temperature in the second stage (intermediate temperature stage) is 0.7 to 0.8 times that of the third stage, and is close to that of the third stage. This application reduces the temperature difference between the inside and outside of the matrix material by gradually increasing the temperature in stages, thereby reducing the generation of thermal stress and slowing down the volume change of the matrix material, thus reducing the internal stress caused by the volume change. The reduction of internal and thermal stress effectively reduces the generation of defects in the matrix material and improves the crystal quality of the matrix material. Furthermore, gradually increasing the temperature in stages also facilitates the full reaction between the lithium source and the ternary precursor, reducing the residual alkali content. Moreover, gradually increasing the temperature in stages also facilitates the full and uniform reaction between the dopant and the ternary precursor, enabling the dopant elements to be uniformly distributed in the ternary cathode material, better exerting the doping modification effect, and improving the structural stability of the ternary cathode material.

[0036] Specifically, the temperature of the second stage can be 460℃~520℃, which is beneficial for reducing defects in the matrix material and ensuring sufficient reaction between the lithium source and the ternary precursor. The temperature of the second stage can, for example, be 460℃, 470℃, 480℃, 500℃, 510℃, 520℃, or any value within the range of any two of the above values. The duration of the second stage can be 10h~20h, which is beneficial for sufficient reaction between the lithium source and the ternary precursor. The duration of the second stage can, for example, be 10h, 11h, 12h, 13h, 14h, 15h, 18h, 20h, or any value within the range of any two of the above values.

[0037] In some embodiments, the heating rate from the temperature of the first stage to the temperature of the second stage is 0.5℃ / min to 1℃ / min. A lower heating rate is beneficial for slow heating, further reducing the generation of thermal stress and internal stress, and thus improving the crystal quality of the matrix material. This heating rate can, exemplarily, be 0.5℃ / min, 0.6℃ / min, 0.7℃ / min, 0.8℃ / min, 0.9℃ / min, 1℃ / min, or any value within the range of any two of the above values.

[0038] The third stage, the main temperature zone, is a crucial stage for the densification and homogenization of the matrix material crystals. During this stage, the grains continue to grow and form a dense and uniform structure, which is beneficial for improving the structural stability and cycle stability of the matrix material.

[0039] Specifically, the temperature of the third stage can be 300℃~700℃. Compared with the temperature of traditional high-temperature sintering, the temperature of the third stage is lower, which is conducive to the formation of a dense and uniform crystal structure, reducing crystal defects and lowering costs. The temperature of the third stage can be, for example, 300℃, 400℃, 450℃, 500℃, 550℃, 600℃, 650℃, 700℃, or any value within the range of any two of the above values. The duration of the third stage can be 20h~30h, and the duration of the second stage can be, for example, 20h, 21h, 22h, 23h, 24h, 25h, 28h, 30h, or any value within the range of any two of the above values. The strategy of "lower main temperature zone combined with longer holding time" in the third stage is beneficial for obtaining ternary cathode materials with uniform and dense crystal particles.

[0040] In some embodiments, the heating rate from the second stage temperature to the third stage temperature is 5°C / min to 7°C / min. A moderate heating rate is beneficial for balancing production efficiency and uniform heating. This heating rate can, exemplarily, be 5°C / min, 5.5°C / min, 6°C / min, 6.5°C / min, 7°C / min, or any value within the range of any two of the above values.

[0041] The temperature in the fourth stage (temperature-controlled cooling stage) is 0.3 to 0.4 times that of the third stage. During this stage, the temperature is maintained for a certain period of time for annealing, which can repair some defects in the matrix material, make the crystal structure more complete, and avoid problems such as internal stress, cracking or performance degradation in the matrix material caused by a rapid drop in temperature.

[0042] Specifically, the temperature of the fourth stage can be 200℃~260℃, which is beneficial for controlling the cooling annealing temperature and repairing defects in the matrix material. The temperature of the fourth stage can, for example, be 210℃, 220℃, 230℃, 240℃, 250℃, 260℃, or any value within the range of any two of the above values. The duration of the fourth stage can be 8h~15h, which is beneficial for the matrix material to be fully repaired and for the release of internal stress. The duration of the fourth stage can, for example, be 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, or any value within the range of any two of the above values.

[0043] In some embodiments, the cooling rate from the third stage temperature to the fourth stage temperature is 0.5℃ / min to 5℃ / min, which facilitates a smoother and more uniform phase transformation process during the single sintering, effectively reducing or even eliminating microcracks within the particles. This cooling rate can, exemplarily, be 0.5℃ / min, 1℃ / min, 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min, or any value within the range of any two of the above values.

[0044] After the fourth stage, this step also includes cooling the matrix material with the furnace to 20°C~100°C. That is, after one sintering is completed, the sintering device (e.g., box furnace) should not be opened immediately. The furnace door should be opened only after the temperature inside the furnace drops to 100°C or below to prevent the matrix material from reacting with H2O and CO2 in the air, which is beneficial to further reduce the alkali content.

[0045] Step S3: Mix the matrix material and the coating material to obtain a second mixture.

[0046] Specifically, the matrix material and the coating material are mixed uniformly using a dry mixing method to obtain a second mixture. It is understood that the mixing method includes, but is not limited to, dry mixing; any method that achieves uniform mixing of the materials is acceptable.

[0047] Step S4: The second mixture is sintered a second time to form a coating layer on the surface of the matrix material, thereby obtaining a ternary cathode material.

[0048] Forming a coating layer on the surface of the substrate material can improve the structural stability of the ternary cathode material, improve the interfacial performance between the ternary cathode material and the solid electrolyte, and form a buffer layer between the substrate material and the solid electrolyte, thereby improving the ionic conductivity of the ternary cathode material, promoting electron transfer and lithium ion diffusion, stabilizing the surface structure, reducing direct contact between the ternary cathode material and the electrolyte, and reducing gas evolution.

[0049] In some embodiments, the coating material may include a solid electrolyte. The solid electrolyte, on the one hand, isolates the matrix material from direct contact with the electrolyte, improving interfacial stability; on the other hand, the solid electrolyte has high ionic conductivity, which guides lithium ions to uniformly embed and extract on the surface of the matrix material particles, reducing local stress and suppressing the generation and propagation of intergranular cracks in the matrix material, thereby effectively improving the cycle life of the ternary cathode material. Furthermore, the ionic conductivity S of the solid electrolyte can satisfy: S≥10 -4 S / cm is beneficial for the rapid transport of lithium ions on the surface of ternary cathode materials.

[0050] For example, the solid electrolyte may include at least one of sulfide solid electrolyte, oxide solid electrolyte and halide solid electrolyte, such as Li2ZrCl6 or Li3YCl6.

[0051] In some embodiments, the dopants in the matrix material can not only interact strongly with oxygen in the matrix material to form strong bonds (e.g., BO, Si-O, or PO), thus improving the structural stability within the matrix material, but also simultaneously interact strongly with elements in the coating layer (e.g., oxygen, sulfur, or chlorine) to form strong bonds (e.g., B-Cl, BS, or BO), thereby increasing the bonding force between the matrix material and the coating layer, improving the stability of the coating layer, and ultimately enhancing the long-term cycling performance of the ternary cathode material.

[0052] In some embodiments, the secondary sintering temperature is 300℃~600℃, during which the substrate material surface reacts strongly with the coating material, allowing the coating material to form a strong and uniform coating layer on the substrate material surface, thereby improving the stability of the coating layer. The secondary sintering temperature can, for example, be 300℃, 350℃, 400℃, 450℃, 500℃, 550℃, 600℃, or any value within the range of any two of the above values.

[0053] In some embodiments, the secondary sintering time can be 5h to 10h, which is beneficial to the strong bonding between the matrix material and the coating layer. The time of the fourth stage can be, for example, 5h, 6h, 7h, 8h, 9h, 10h or any value within the range of any two of the above values.

[0054] Compared with existing technologies, the preparation method of the ternary cathode material in this application has the following advantages: 1. Gradient sintering is employed, with staged temperature control during the primary sintering process. By precisely controlling the temperature at each stage, the lithium source and ternary precursor react fully, reducing residual alkali content. This eliminates the need for a water washing process, avoiding damage to the ternary cathode material structure and lowering production costs. Simultaneously, gradient sintering improves the crystal density and uniformity of the ternary cathode material, enhancing its cycle stability. Furthermore, gradient sintering allows for a more complete and uniform reaction between the dopant and the ternary precursor, improving the doping modification effect.

[0055] 2. Forming a coating layer on the surface of the substrate material can, on the one hand, isolate the substrate material from direct contact with the electrolyte and improve interface stability; on the other hand, the coating layer can guide lithium ions to be uniformly inserted and extracted on the surface of the substrate material particles, reduce local stress, and inhibit the generation and propagation of intergranular cracks in the substrate material, thereby effectively improving the cycle life of the ternary cathode material.

[0056] 3. The doping elements in the matrix material can not only interact strongly with the oxygen element in the matrix material to form strong bonds and improve the internal structural stability of the matrix material, but also interact strongly with the elements in the coating layer to form strong bonds, thereby improving the bonding force between the matrix material and the coating layer, improving the stability of the coating layer, and thus improving the long-term cycle performance of the ternary cathode material.

[0057] Based on the same inventive concept, this application also provides a ternary cathode material, which is prepared by the aforementioned preparation method. The ternary cathode material includes a matrix material containing doped elements and a coating layer on the surface of the matrix material.

[0058] Compared with existing technologies, the ternary cathode material of this application has advantages such as low cost, low residual alkali content, high energy density, high cycle stability and long cycle life, which is conducive to the large-scale application of ternary cathode materials.

[0059] This application also provides an electrochemical device (e.g., a battery) comprising a positive electrode sheet, the positive electrode sheet comprising a positive electrode material, wherein the positive electrode material is the aforementioned ternary positive electrode material. The ternary positive electrode material has less residual lithium on its surface, which is beneficial for improving the safety of the electrochemical device and reducing the risk of gas generation and bulging during cycling.

[0060] The electrochemical device can be exemplarily a solid-state lithium-ion battery, in which the positive electrode and the solid electrolyte interface have good contact. Furthermore, compared to liquid lithium-ion batteries, solid-state lithium-ion batteries can further improve battery energy density, addressing the "range anxiety" problem in the field of new energy electric vehicles. Simultaneously, solid-state lithium-ion batteries also have the advantages of being non-flammable and leak-proof, effectively improving battery safety performance.

[0061] Compared with the prior art, the electrochemical device provided in this application has higher cycle stability, longer cycle life and better safety.

[0062] The present application's solution will be explained below with reference to embodiments. Those skilled in the art will understand that the following examples are for illustrative purposes only and should not be construed as limiting the scope of the application. Unless otherwise stated, reagents, software, and instruments involved in the following embodiments that are not specifically described are all conventional commercially available products or publicly disclosed.

[0063] Example 1 Step S1: Add the ternary precursor Ni 0.87 Co 0.06 Mn 0.07 (OH)2, lithium hydroxide and B2O3 are mixed to obtain a first mixture, wherein the molar ratio of Li in lithium hydroxide to nickel, cobalt and manganese in the ternary precursor, Li / Me, is 1.03, and the amount of B2O3 added is 0.03 wt% of the ternary precursor.

[0064] Step S2: The first mixture is sintered once to obtain the matrix material. The first sintering includes a first stage, a second stage, a third stage, and a fourth stage in sequence. The first mixture is first heated to the first stage temperature of 250°C at a heating rate of 10°C / min and held for 3 hours. Then, it is heated to the second stage temperature of 500°C at a heating rate of 0.5°C / min to 1°C / min and held for 5 hours. Then, it is heated to the third stage temperature of 650°C at a heating rate of 6°C / min and held for 20 hours. Finally, it is cooled to the fourth stage temperature of 250°C at a cooling rate of 1°C / min and held for 6 hours to obtain the matrix material. The matrix material is then removed from the furnace after it has cooled naturally to 100°C.

[0065] Step S3: Mix the matrix material and Li2ZrCl6 to obtain a second mixture, wherein the amount of Li2ZrCl6 added is 0.05 wt% of the matrix material.

[0066] Step S4: The second mixture is sintered at 400°C for 6 hours to form a coating layer of Li2ZrCl6 on the surface of the matrix material, thus obtaining a ternary cathode material.

[0067] Example 2: The difference from Example 1 is that the coating material in step S3 is Li3YCl6. The preparation methods of the remaining ternary cathode materials are basically the same as those in Example 1.

[0068] Comparative Example 1: The difference from Example 1 is that no dopant B2O3 is added in step S1. The preparation methods of the remaining ternary cathode materials are basically the same as those in Example 1.

[0069] Comparative Example 2: The difference from Example 1 is that in step S2, the first sintering involves directly heating the first mixture to 650°C at a heating rate of 6°C / min and holding it at that temperature for 20 hours, then cooling it to 250°C at a cooling rate of 1°C / min and holding it at that temperature for 6 hours to obtain the matrix material. The matrix material is then allowed to cool naturally to 100°C before the furnace door is opened and the matrix material is removed. The preparation methods for the remaining ternary cathode materials are basically the same as in Example 1.

[0070] Comparative Example 3 The difference from Example 1 is that step S3 is omitted, i.e., no coating material is added. The preparation methods for the remaining ternary cathode materials are basically the same as those in Example 1.

[0071] The following tests were conducted on the ternary cathode materials obtained in Examples 1-2 and Comparative Examples 1-3 and the batteries prepared from the ternary cathode materials.

[0072] 1. Scanning electron microscopy (SEM) test: A scanning electron microscope (model: Sigma360) with high-resolution imaging capability was used to observe the microscopic morphology and structural features of the material slices magnified 3000 times.

[0073] 2. Free lithium content test: The test was conducted using a potentiometric titrator and the method specified in the standard "Determination of Magnetic Foreign Matter Content and Residual Alkali Content in Cathode Materials of Lithium-ion Batteries" drafted by the National Technical Committee on Standardization of Nonferrous Metals.

[0074] 3. Electrochemical performance testing: Battery preparation: Ternary cathode material, conductive agent SP and binder PVDF are mixed evenly in a mass ratio of 90:5:5 to prepare a half cell.

[0075] First charge / discharge specific capacity test: The LAND battery testing system was used for constant current charge / discharge testing. During the test, the working voltage range for the first discharge capacity test was 2.8V~4.35V, the temperature was 25℃, the charge / discharge rate was +0.1C / -0.1C, the CV cutoff current was 0.01C, and the first coulombic efficiency (referred to as first efficiency, first efficiency = first discharge specific capacity / first charge specific capacity) and the first discharge specific capacity of the battery were measured.

[0076] High-temperature cycle performance test: At 45℃, the half-cell was subjected to 1C / 1C charge-discharge cycles, with an operating voltage range of 2.8V-4.35V and a CV cutoff current of 0.01C, to test the cycle retention rate of the battery.

[0077] The preparation parameters and test results of Examples 1-2 and Comparative Examples 1-3 are shown in Table 1 and 2. Figures 2 to 4 As shown.

[0078] Table 1 The above results indicate that: Please combine Figure 2 Table 1 compares and analyzes the free lithium content of Examples 1-2 and Comparative Examples 1-3. Examples 1-2 both used gradient sintering, resulting in a low free lithium content in the ternary cathode material, approximately 1000 ppm. Comparative Example 2 used a conventional sintering method, increasing the free lithium content in the ternary cathode material to approximately 1500 ppm. The main reason is that in Examples 1-2, gradient sintering removes impurities in the first stage and then gradually increases the temperature to the second and third stages, reducing internal stress caused by volume changes and thermal stress caused by sudden temperature changes, thus reducing crystal defects. This allows the lithium source and the ternary precursor to react fully, resulting in a ternary cathode material with a low free lithium content.

[0079] Please combine Figure 3 As shown in Table 1, Example 1, using internal doping and external coating of the substrate material, maintained a capacity retention of 93.2% after 100 high-temperature cycles. Comparative Example 3, using an uncoated cathode material, showed a capacity retention of only 85.5% after 100 high-temperature cycles. The comparison between Example 1 and Comparative Example 3 demonstrates that coating the substrate material surface can, on the one hand, isolate the substrate material from direct contact with the electrolyte, improving interfacial stability and thus enhancing cycle stability; on the other hand, combined with… Figure 4 Comparing the ternary cathode material slices after cycling in Example 1 and Comparative Example 3, the Li2ZrCl6 coating layer with high ionic conductivity can guide lithium ions to be uniformly inserted and extracted on the surface of the ternary cathode particles, reduce local stress, and inhibit the generation and propagation of intergranular cracks, thereby further improving cycle life.

[0080] In addition, although both Example 1 and Comparative Example 1 were coated, Comparative Example 1 was not doped. The capacity retention rate of Comparative Example 11 was lower than that of Example 1. This is because the doping element interacts strongly with the oxygen on the surface of the ternary cathode material and the chlorine in the coating layer to form BO and B-Cl bonds. The synergistic effect of the two further enhances the adhesion of the coating layer and improves the stability of the coating layer, thereby further improving the long-term cycle performance of the ternary cathode material.

[0081] It is understood that the above embodiments are merely exemplary implementations used to illustrate the principles of the present invention, and the present invention is not limited thereto. For those skilled in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.

Claims

1. A method for preparing a ternary cathode material, characterized in that, The method comprises: mixing a ternary precursor, a lithium source and a doping material to obtain a first mixture; sintering the first mixture once to obtain a base material, the sintering once comprising a first stage, a second stage, a third stage and a fourth stage in sequence, wherein the temperature of the first stage and the temperature of the fourth stage are 0.3-0.4 times the temperature of the third stage, and the temperature of the second stage is 0.7-0.8 times the temperature of the third stage; mixing the base material and a coating material to obtain a second mixture; and sintering the second mixture twice to form a coating layer on the surface of the base material from the coating material, to obtain the ternary positive electrode material.

2. The production method according to claim 1, wherein The temperature of the third stage is 300-700℃, and the time of the third stage is 20-30h.

3. The production method according to claim 2, wherein The temperature of the first stage is 200-260℃, and the time of the first stage is 10-15h; The temperature of the second stage is 460-520℃, and the time of the second stage is 10-20h; The temperature of the fourth stage is 200-260℃, and the time of the fourth stage is 8-15h.

4. The production method according to claim 1, wherein The preparation method satisfies at least one of the following conditions: (1) the heating rate of the first mixture from room temperature to the temperature of the first stage is 10-20℃ / min; (2) the heating rate of the first stage from the temperature of the first stage to the temperature of the second stage is 0.5-1℃ / min; (3) the heating rate of the second stage from the temperature of the second stage to the temperature of the third stage is 5-7℃ / min; (4) the cooling rate of the third stage from the temperature of the third stage to the temperature of the fourth stage is 0.5-5℃ / min.

5. The production method according to claim 1, wherein After the fourth stage, the step of obtaining the base material further comprises: cooling the base material in the furnace to 20-100℃.

6. The production method according to claim 1, wherein The doping element in the doping material comprises at least one of Si, B and P.

7. The production method according to claim 1, wherein The coating material comprises a solid-state electrolyte.

8. The production method according to claim 7, wherein The solid-state electrolyte comprises at least one of a sulfide solid-state electrolyte, an oxide solid-state electrolyte and a halide solid-state electrolyte.

9. A ternary cathode material, characterized in that, The ternary positive electrode material is prepared by the preparation method of any one of claims 1-8, and comprises a base material containing a doping element and a coating layer on the surface of the base material.

10. An electrochemical device, characterized by, The electrochemical device comprises a positive electrode sheet, and the positive electrode sheet comprises a positive electrode material, which is the ternary positive electrode material of claim 9.